VUV photoionization of the CH2NC radical: adiabatic ionization energy and cationic vibrational mode wavenumber determinations. Issue 22 (26th May 2020) - Gans, Bérenger; Hartweg, Sebastian; Garcia, Gustavo A.; Boyé-Péronne, Séverine; Harper, Oliver J.; Guillemin, Jean-Claude; Loison, Jean-Christophe
Abstract : The photoelectron spectroscopy of CH2 NC (isocyanomethyl) radical species is investigated for the first time between 9.3 and 11.2 eV in the vicinity of the first photoionizing transition X +1 A1 ← X  2 B1 . Abstract : The photoelectron spectroscopy of CH2 NC (isocyanomethyl) radical species is investigated for the first time between 9.3 and 11.2 eV in the vicinity of the first photoionizing transition X +1 A1 ← X  2 B1 . The experiment combines a microwave discharge flow-tube reactor to produce the radicals through the CH3 NC + F → CH2 NC + HF reaction, a VUV synchrotron radiation excitation, and a double imaging electron/ion coincidence spectrometer which allows the recording of mass-selected threshold photoelectron spectra. Assignment of the observed vibrational structure of the CH2 NC + cation is guided by ab initio calculations and Franck–Condon simulations. From the experimental spectrum, the first adiabatic ionization energy of the CH2 NC radical is measured as 9.439(6) eV. Fundamental wavenumbers are determined for several vibrational modes of the cation:  1 + (CH2 symmetric stretch) = 2999(80) cm −1,  2 + (NC stretch) = 1925(40) cm −1,  4 + (H2 C–N stretch) = 1193(40) cm −1,  6 + (CNC out-of-plane bend) = 237(50) cm −1, and  8 + (CH2 rock) = 1185(60) cm −1 .